Membingkai â€œEpistemeâ€ Ilmu Dakwah - Shodikin, Asep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
One of urgent task in developing science of da’wah is seek what is foundation to it. Because of the foundation so that the science of da’wah having a clear of frame of think. One of the foundations is named epistemology, a foundation of science that study how the science is got and developed. Based on it’s developing, epistemecally the science of da’wah as developed through three methods: dig up the science from Islamic doctrine source and muslim intellectual tradition (thuruqul istinbath), accepting the social science elements and modern technology (thuruqul iqtibash), and a set of research (thuruqul istiqra’).